Development of Principal Strategy Model in Mitigating Student Violence in Elementary Schools - Syafaruddin, Baso; Mansur, Mansur; Suriana, Suriana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study explores the efforts of the school principal in mitigating student violence at public elementary school 204 Sompe, Sabangparu District, Wajo Regency, through educational and da'wah-based approaches. It aims to describe the strategies employed by the principal to reduce physical, psychological, and verbal violence in the school, as well as the supporting factors and challenges faced in these efforts. The research was conducted using a descriptive, non-statistical analysis with an inductive approach. Data were collected and analyzed through deductive and inductive methods. Key findings highlight the principal’s comprehensive approach, which includes problem identification, policy formulation, partnership building, goal-setting, implementation, and evaluation. Supporting factors include the school’s location in a region known for its Islamic culture, extracurricular activities, and manageable student numbers. Challenges include resistance from students, particularly those with limited religious exposure at home, and the influence of technology on student behavior. This study contributes to understanding how educational and da'wah approaches can mitigate student violence in schools, providing insights for further research and improvements in educational practices.